The relationship between creative thinking and motivation to learn creative thinking among pre-schoolers in Jordan - Al-Zu’bi, Mohammad Ahmad Abdelaziz; Omar Fauzee, Mohd Sofian; Kaur, Amrita (Open Access Publishing Group, 2017)
The investigation of the level of creative thinking and motivation to learn creative thinking, and the relationship between both of them, in Jordan is still insufficient due to lack of interest and research among researchers and scholars. Therefore, this study examines the relationship between creative thinking and motivation to learn creative thinking among pre-school children in Jordan. A total of 102 students from one kindergarten was examined. Parental consent was obtained before the study was conducted. The result from the analysis posited that there is a medium level of motivation to learn creative thinking (64.7%). The means of TCAM scores and its dimensions were: TCAM overall score (M= 68.24, SD= 14.615), Fluency (M= 17.53, SD= 4.776), Originality (M= 25.7, SD= 8.264), and Imagination (M= 25.01, SD= 3.793). In addition, there is a positive statistically significant correlation (0.573) among the total of creative thinking scores and the total of motivation to learn creative thinking. Spearman correlation was used to evaluate the overall relationship between creative thinking and motivation to learn creative thinking. A strong positive correlation was found between creative thinking and motivation to learn creative thinking scores of pre-school children. The present study has also discussed the findings, the limitations and the recommendations.